Hypoxic Repeat Sprint Training Improves Rugby Player's Repeated Sprint but Not Endurance Performance - Hamlin, Michael J.; Olsen, Peter D.; Marshall, Helen C.; Lizamore, Catherine A.; Elliot, Catherine A. (Frontiers in Physiology, 2017)
This study aims to investigate the performance changes in 19 well-trained male rugby players after repeat-sprint training (six sessions of four sets of 5 x 5 s sprints with 25 s and 5 min of active recovery between reps and sets respectively) in either normobaric hypoxia (HYP; n = 9; FIO2 = 14.5%) or normobaric normoxia (NORM; n = 10; FIO2 = 20.9%). Three weeks after the intervention, 2 additional repeat-sprint training sessions in hypoxia (FIO2 = 14.5%) was investigated in both groups to gauge the efficacy of using ‘top-up’ sessions for previously hypoxic-trained subjects and whether a small hypoxic dose would be beneficial for the previously normoxic-trained group. Repeated sprint (8 x 20m) and Yo-Yo Intermittent Recovery Level 1 (YYIR1) performances were tested twice at baseline (Pre 1 and Pre 2) and weekly after (Post 1-3) the initial intervention (intervention 1) and again weekly after the second ‘top-up’ intervention (Post 4-5). After each training set, heart rate, oxygen saturation and rate of perceived exertion were recorded. Compared to baseline (mean of Pre 1 and Pre 2), both the hypoxic and normoxic groups similarly lowered fatigue over the 8 sprints one week after the intervention (Post 1: -1.8 ± 1.6%, -1.5 ± 1.4%, mean change ± 90% CI in HYP and NORM groups respectively). However, from Post 2 onwards, only the hypoxic group maintained the performance improvement compared to baseline (Post 2: -2.1 ± 1.8%, Post 3: -2.3 ± 1.7%, Post 4: -1.9 ± 1.8%, and Post 5: -1.2 ± 1.7%). Compared to the normoxic group, the hypoxic group was likely to have substantially less fatigue at Post 3-5 (-2.0 ± 2.4%, -2.2 ± 2.4%, -1.6 ± 2.4% Post 3, Post 4, Post 5 respectively). YYIR1 performances improved throughout the recovery period in both groups (13-37% compared to baseline) with unclear differences found between groups. The addition of two sessions of ‘top-up’ training after intervention 1, had little effect on either group. Repeat-sprint training in hypoxia for 6 sessions increases repeat sprint ability but not YYIR1 performance in well-trained rugby players.